Fixed Points of Nonlinear and Asymptotic Contractions in the Modular Space - A. Razani; E. Nabizadeh; M. Beyg Mohamadi; S. Homaei Pour (Abstract and Applied Analysis)
A fixed point theorem for nonlinear contraction in the modular space is proved. Moreover, a fixed point theorem for asymptotic contraction in this space is studied.